FRI0549 Predictive Factors of Remission in Juvenile Idiopathic Arthritis Patients Treated with Biological Therapies. 13-Year Experience of A Single Center. (10th June 2014) - Romano, M.; Pontikaki, I.; Ardoino, I.; Gattinara, M.; Del Giudice, E.; Boracchi, P.; Lodi-Rizzini, S.; Meroni, P.L.; Gerloni, V.
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) is the most prevalent chronic rheumatic disease in childhood. The term JIA means a group of clinically heterogeneous arthritides, beginning before the age of 16 years, of unknown cause, and persistent for more then 6 weeks. The prognosis is often severe and many children are still suffering from active disease in adulthood. Objectives: Juvenile Idiopathic Arthritis (JIA) is the most prevalent chronic rheumatic disease in childhood. The term JIA means a group of clinically heterogeneous arthritides, beginning before the age of 16 years, of unknown cause, and persistent for more then 6 weeks. The prognosis is often severe and many children are still suffering from active disease in adulthood. Methods: All JIA patients (pts) treated in our Center with BTs, are prospective followed every 2 months for the evaluation of safety and efficacy (according to ACR-Pedi core set criteria). Charts of all 363 pts enrolled between November 1999 and November 2012, have been reviewed. In total 750 BTs were administered to our 363 pts. The outcome measures needed to define the achievement of the status of ID, CRM and CR, at several follow-up moments, were analysed. Results: Two hundred ninety-four JIA pts (who received in total 535 BT) were statistically evaluated for predicting factors of CRM during the 1st course of BT. Median age at disease onset was 5.4 yrs (mean 6.7, range 0.5-16). At starting of the 1st BT median disease duration was 7.9 yrs (mean 9.6, range 0.2 - 41.4), median age was 15.2 yrs (mean 16.3, range 1.9 - 49.8). Median treatment duration of the 1st BT was 2.06 yrs (mean 1.96, range 0.03-10.35). CRM was achieved with 172 out of all 535 BTs (32.1%) and with 136 out of 294 1st courses of BTs (46.2%). 136 out of 172 successful treatments (79.1%) were 1st BTs. During the 1st BT, 136 out of 294 pts (46.3%) obtained one or more periods of CRM of variable duration. Only 4 pts reached CR. The statistical multivariate analysis showed that the probability of CRM with the 1st BT is positively correlated with male gender (p=0.005), non-soJIA (p<0.05) and shorter disease duration before starting the 1st BT (p<0.05). Conclusions: Upon treatment with the 1st BT, nearly half of children and young people affected by JIA, although they had suffered from long-standing, refractory disease non responder to DMARDs, reached at least one sustained period of CRM. Nevertheless a persistent CR off medication remains a rare event. References: Wallace CA, Ruperto N, Giannini EH. Preliminary criteria for clinical remission for select categories of juvenile idiopathic arthritis. J Rheumatol 2004;31:2290-4. Lurati A, Salmaso A, Gerloni V, Gattinara M, Fantini F. Accuracy of Wallace criteria for clinical remission in juvenile idiopathic arthritis: a cohort study of 761 consecutive cases. J Rheumatol. 2009 Jul;36(7):1532-5. Fantini F, Gerloni V, Gattinara M, Cimaz R, Arnoldi C, Lupi E. Remission in juvenile chronic arthritis: a cohort study of 683 consecutive cases with a mean 10 year followup. J Rheumatol. 2003 Mar;30(3):579-84. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5504